ULTRASONOGRAPHIC IMAGING OF KIDNEYS IN MALE BUFFALO CALVES - Khunt, Parul; Mistry, JN; Jhala, SK; Suthar, DN; Patel, MD (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The study was conducted on 24 male buffalo calves aged 4-8 months weighing between 55 and 75 kg to document the ultrasonographic imaging and measurements of kidneys. Both kidneys were entirely assessed through right paralumbar fossa. Cranial pole of right kidney was visible by placing probe at proximal part of last intercostal space. Cranial pole of left kidney was observed percutaneously through right paralumbar fossa in all calves while caudal pole was invisible due to rumen and intestinal loops. Horizontal diameter of right kidney was higher than the vertical diameter. Convex probe (5.0 MHz) was better for percutaneous examination of left and right kidney. Images formed by percutaneous examination of right kidney through right paralumbar fossa using 6.5 MHz linear rectal probe were of higher magnification and better resolutions as compared to convex probe (3.5 and 5.0 MHz).
Keywords: Buffalo calves; Kidney; Ultrasonography; Urinary system